Collaboration on Art Educators' Perceptions of Required Professional Learning. (3rd July 2021) - Anderson, Kyle
Abstract : In this action research study, we investigate the impact that social collaborative professional learning activities have on art educators' perceptions of required professional development on art assessment. The study was conducted in the context of a district-wide professional development program and evaluated through a performance-based assessment professional learning activity, which was done in both a collaborative and one-on-one format. The findings indicate that participant-led professional learning supports visual arts teachers' engagement in and understanding of professional development content. Reflective dialogue, networking opportunities, and collaborative cultures were key factors contributing to the outcomes of this study. In addition to outlining the study, we discuss other considerations for future research and implications for professional development for art teachers.